Free-Standing SnO2@rGO Anode via the Anti-solvent-assisted Precipitation for Superior Lithium Storage Performance - Jiang, Shuli; Huang, Ruiming; Zhu, Wenchang; Li, Xiangyi; Zhao, Yue; Gao, Zhixiang; Gao, Lijun; Zhao, Jianqing (Frontiers in Chemistry, 2019)
Metal oxides have been attractive as high-capacity anode materials for lithium-ion batteries. However, oxide anodes encounter drastic volumetric changes during lithium ion storage through the conversion reaction and alloying/dealloying processes, leading to rapid capacity decay and poor cycling stability. Here, we report a free-standing SnO2@reduced graphene oxide (SnO2@rGO) composite anode, in which SnO2 nanoparticles are tightly wrapped within wrinkled rGO sheets. The SnO2@rGO sheet is assembled in high porosity via an anti-solvent-assisted precipitation of dispersed SnO2 nanoparticles and graphene oxide sheets in the distilled water, followed by the filtration and post-annealing processes. Significantly enhanced lithium storage performance has been obtained of the SnO2@rGO anode compared with the bare SnO2 anode material. A high charge capacity above 700 mAh g−1 can be achieved with a satisfying 95.6% retention after 50 cycles at a current density of 500 mA g−1, superior to reserved 126 mAh g−1 and a much lower 16.8% retention of the bare SnO2 anode. XRD pattern and HRTEM images of the cycled SnO2@rGO anode material verify the expected oxidation of Sn to SnO2 at the fully-charged state in the 50th cycle. In addition, FESEM and TEM images reveal the well-preserved free-standing structure after cycling, which accounts for high reversible capacity and excellent cycling stability of such a SnO2@rGO anode. This work provides a promising SnO2-based anode for high-capacity lithium-ion batteries, together with an effective fabrication adoptable to prepare different free-standing composite materials for device applications.